Animal Models with Metabolic Syndrome Markers Induced by High Fat Diet and Fructose - Larantika Hidayati; Agung Dwi Wahyu Widodo; Boerhan Hidayat (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2020)
Metabolic syndrome is lipid and non-lipid metabolism disorder due to the association of several factors such as physiological, clinical, biochemical, and interrelated factors. People with metabolic syndrome can be diagnosed by fulfilling 3 of 5 criteria, including obesity and increased waist circumference, increased TG levels, increased blood pressure, hyperglycemia, and increased High-Density Lipoprotein (HDL) serum. The high-fat diet disrupts tissue lipid metabolism, so insulin resistance occurs due to lipotoxicity. Besides, some studies use a combination of mixtures (fructose, sucrose) and fat-rich food components to build metabolic characteristics in mice that affect human characteristics. The purpose of this study was to make an animal model with a metabolic syndrome marker induced by the High Fat Diet (HFD) consisting of pork oil and chicken egg yolk, as well as fructose from simple and economical ingredients. This study was an experimental study using experimental animals of male Rattus norvegicus strain wistar, which were grouped into three random treatment groups, namely the control group, HFD group, and High Fat Diet Fructose (HFDF) group. The number of samples used was 27 rats, with nine rats in each group. The animal was induced for four weeks, then measured levels of FPG, HD, and TG. From the research that has been done, it is found that there are significant differences in levels of Fasting Plasma Glucose (FPG), High-Density Lipoprotein (HDL), and Triglycerides (TG) (p